International monetary system: issues and areas of reforms - V. V. Kuznetsova (Мир новой экономики, 2018)
The article investigates issues of the modern international monetary system occurred due to dollar’s domination, and relevant forming risks for states members, and exams suggested measures for their elimination and solution. IMF inclusion of renminbi into the SDR currency basket is a step forward creation of the new multi reserve currency system. The IMF’s verdict is a compromise as such. On one side, its compelling reasons include the rising rations of the Chinese economy in world economy, and the Chinese currency in international settlements. On the other side, the Chinese currency is not free usable currency still, and its exchange rate is not governed by market. Whether update world monetary system would obtain additional stability or contrary increase risks depends on many factors including sovereign states’ ability to cooperative behavior.